Durata e costo delle visite in medicina generale: il progetto DYSCO - Garattini, Livio; Castelnuovo, Emanuela; Lanzeni, Davide; Viscarra, Cecilia; Gruppo di studio DYSCO VISITE, DYSCO VISITE (Farmeconomia. Health Economics and Therapeutic Pathways, 2003)
In Italy, general practitioners (GPs) operating within the National Health Service (NHS) are paid according to the number of patients followed, without relation to the number of visits performed. This means that, from a theoretical point of view, the marginal cost of an adjunctive medical examination equals to zero. Since this view is clearly little realistic, in this paper we expose a methodological approach to estimate the real cost of a GP visit, starting from data collected in the DYSCO study, a national survey on the medical costs of dystimia in Italy. 46 GPs were asked to record the number and duration of ambulatory and domiciliar visits, along with the time spent in administrative tasks, during 4 weeks, each randomly chosen within a season (spring, summer, autumn, winter). In order to assign a monetary value to each visit, the total fee reimbursed by the NHS to a GP was divided by the total time spent on work, and then again by the number of visits conducted during this time. The calculations performed revealed that the mean duration of a ambulatory visit amounts to about 10 minutes, while a domiciliar visit (including travelling time) lasts almost the double. An interesting result was that summer visits have significantly longer duration than the mean, and consequently cost more. The mean cost of a GP’s ambulatory visit resulted about 12 Euro; a domiciliar visit costs almost 23 Euro. The times and costs calculated in this study are consistent with other calculations performed by other authors in Europe and Italy, confirming the appropriateness of the employed methodology.